Głosy współczesnych dzieci w sprawie "Kajtusia Czarodzieja" – śladem Korczakowskiego pisarskiego eksperymentu - Marzenna Nowicka (Problemy Wczesnej Edukacji)
Janusz Korczak engaged children in writing novels intended for them. His writing experiments consisted in directly transferring children’s ideas to the paper, correcting and reworking the stories under the influence of the listeners’ comments, removing and cutting fragments of the text at their request. Following Korczak’s method, a reconstruction of understanding by modern children of created 85 years ago novel “Kajtuś Czarodziej” was made. Based on focus interviews, it was established that the fairytale context of reading is read by children on a multithreaded basis, filtered by reference to the present day, critically evaluated by older children. The linguistic layer is acceptable, while the transfer of the fairytale aspect to real life does not suit the contemporary young recipients. The children’s suggestions regarding the new plots of reading were mainly of mimetic character in relation to the original.